Transcultural adaptation and theoretical models validation of the Spanish version of the Self-Care of Diabetes Inventory - Martínez-Tofé, Jesús; Ausili, Davide; Soto-Ruiz, Nelia; Santolalla-Arnedo, Iván; Durante, Angela; di Nitto, Marco; Lysanets, Yuliia; de Viñaspre-Hernández, Regina Ruiz; Tejada-Garrido, Clara Isabel; Sánchez Barba, Mercedes; Gea-Caballero, Vicente; Juárez-Vela, Raúl (Frontiers in Medicine, 2024)
Background For patients with diabetes mellitus, self-care is crucial because it prevents complications and helps preserve quality of life. Clinicians and researchers require effective tools for assessing self-care behaviors across various dimensions to identify individual needs and maximize resource allocation. The aim of this study was to evaluate the validity and reliability of the Spanish version of the Self-Care of Diabetes Inventory (SCODI). Methods Two hundred eighteen participants with DMT1 and DMT2 who were recruited through convenience sampling from a university hospital participated in our cross-sectional study. After translation and cultural adaptation, the enrolled patients answered the questions. We performed an exploratory factor analysis (EFA) on each of the SCODI scales and Confirmatory factor analysis (CFA) was performed using our models which appropriate fit indices. Results The original structure of the four-dimensions tool was confirmed. The overall consistency across the four scales was assessed by Cronbach’s alpha: self-care maintenance (0.766), self-care monitoring (0.790), self-care management (0.771), and self-care confidence (0.936). The model fit yielded a chi-square index of 1.028 with 773 degrees of freedom. Confirmatory factor analysis showed a good fit, thereby affirming the reliability of the model. Conclusion The internal consistency and reliability of the SCODI Spanish version are deemed adequate. This tool is appropriate when it is desired to evaluate the self-care practices of Spanish persons suffering from diabetes due to its good psychometric qualities.